Monitoramento in/on-line da malaxagem na extrusão: hidrólise e extensão de cadeia do poli(tereftalato de etileno) e fusão do polipropileno - Bicalho, Luciana Assumpção (2020)
During twin-screw extrusion, understanding and quantifying the behaviour of molten polymers under different conditions is limited by the complex configuration of the equipment. Due to this fact, real-time extrusion monitoring techniques have gained space, among them, the use of optics is quite attractive since its response time is short and there is no disturbance of the analysed medium. This work focused on the study of real-time in/on-line monitoring of polymeric casting during twin-screw extrusion in different malaxation situations by two optical techniques: turbidity and birefringence. A methodology was developed for in-line monitoring of hydrolysis, chain extension and simultaneous occurrence of both reactions for PET in different screw profiles. A specific equipment was also developed to be laterally coupled to the twin-screw extruder, promoting on-line monitoring of PP melting, at different malax points in the extrusion barrel. In the in-line monitoring of the reactions with PET, it was concluded that when evaluating each reaction separately the screw profile with a preferentially dispersive mixture was better for the chain extension reaction; on the other hand, the profile with a distributive character provided a better hydrolysis reaction. The intrinsic viscosity measurements of the samples taken during extrusion corroborated with the results obtained in-line, validating the measurements. In on-line monitoring, the axial melt profile of the PP melt flow during the first malaxation zone was quantified in real time. The melt fraction of PP in the flow was estimated by measuring its turbidity and flow birefringence. The turbidity decreased as the melt developed, as the ratio of the solid-to-fused polymer interfaces decreased. On the other hand, birefringence increased as the melt progressed.